Contrasting effects of music on reading comprehension in preadolescents with and without ADHD. (September 2020) - Madjar, Nir; Gazoli, Rami; Manor, Iris; Shoval, Gal
Highlights: Music improved reading comprehension only among preadolescents with ADHD. Heart rate variability indicated differences in autonomous nervous system responses. Changes in heart rate variability were related to reading comprehension improvement. Results were replicated across two quasi-experimental studies. Music improved attentive skills in ADHD group but not among typically developed. Abstract: Children and adolescents with attention-deficit/hyperactivity disorder (ADHD) are advised to study in quiet settings; yet, many professionals assert that environments devoid of external stimulus, are often unnecessary to facilitate optimal learning conditions. Empirical controlled trials examining this assertion are scarce. This study explored whether music improves reading performance of preadolescents with ADHD compared with typically developed (TD) peers, and its correlation with changes in heart rate variability (HRV), an autonomic nervous system indicator. After a pilot phase ( N = 20; age = 12.05), additional independent sample of ADHD ( n = 25; age = 10.28) and TD ( n = 25; age = 10.44) preadolescents completed reading tasks under four conditions: without background music, with calm music without lyrics, calm music with lyrics, and rhythmic music with lyrics. Reading comprehension and mean-levels of HRV changes (before and during each task) were assessed using validated instruments. Reading comprehension significantly improved under the music conditions in ADHD group and deteriorated among TD. Differences in HRV changes were significant between groups, and explained reading performance. These findings suggest that music may improve attentive skills of preadolescents with ADHD, but not TD, and urge the need to identify an optimal fit between individual and contextual characteristics.